Airplane and parachutes - reverse section - Unidentified artist (Colorado State University. Libraries, 1967)
Reverse of a section of the Airplane and Parachutes.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 2 layers (red, black); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama